Divergent sexual signals reflect costs of local parasites - Hund, Amanda K; Hubbard, Joanna K; Albrecht, Tomáš; Vortman, Yoni; Munclinger, Pavel; Krausová, Simona; Tomášek, Oldřich; Safran, Rebecca J (Evolution; international journal of organic evolution, 2020)
Many closely related populations are distinguished by variation in sexual signals and this variation is hypothesized to play an important role in reproductive isolation and speciation. Within populations, there is considerable evidence that sexual signals provide information about the incidence and severity of parasite infections, but it remains unclear if variation in parasite communities across space could play a role in initiating or maintaining sexual trait divergence. To test for variation in parasite-associated selection, we compared three barn swallow subspecies with divergent sexual signals. We found that parasite community structure and host tolerance to ecologically similar parasites varied between subspecies. Across subspecies we also found that different parasites were costly in terms of male survival and reproductive success. For each subspecies, the preferred sexual signal(s) were associated with the most costly local parasite(s), indicating that divergent signals are providing relevant information to females about local parasite communities. Across subspecies, the same traits were often associated with different parasites, indicating that parasite-sexual signal links are quite flexible and may evolve relatively quickly. This study provides evidence for (1) variation in parasite communities and (2) different parasite-sexual signal links among three closely related subspecies with divergent sexual signal traits, suggesting that parasites may play an important role in initiating and/or maintaining the divergence of sexual signals among these closely related, yet geographically isolated populations.
Keywords: Reproduction; Genetic Fitness; Mating Preference, Animal; Barn swallow; mužské pohlaví; pigmentace; divergence; sexual selection; ženské pohlaví; zvířata; sexuální výběr u zvířat; Host-Parasite Interactions; Tail; genetická zdatnost; Species Specificity; parasites; interakce hostitele a parazita; Swallows; Pigmentation; rozmnožování; local adaptation; ocas; druhová specificita; vlaštovkovití; Female; community; Male; Animals